2019
DOI: 10.1002/cche.10225
|View full text |Cite
|
Sign up to set email alerts
|

Changes in shelf life and quality of fresh hull‐less barley noodles during storage

Abstract: Background and objectives In order to study the quality changes of fresh hull‐less barley noodles (FHBN) during storage, the total plate count (TPC), cooking quality, color, texture, and moisture characteristic of FHBN were investigated at 0 hr, 6 hr, 12 hr, 18 hr, 24 hr, and 30 hr of storage at 25°C. Findings The FHBN deteriorated after storage for 24 hr (TPC was 1.4 × 106 CFU/g), while the fresh wheat noodles (FWN) deteriorated after 18 hr (TPC was 106 CFU/g). In addition, T21 and T22 in FWN were bigger than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…On the one hand, microbial activity destroyed the gel structure of fresh brown rice noodles, and this might weaken the binding ability between water and macromolecules; thus, the strongly bound water was shifted into weakly bound water and free water. On the other hand, water was one of the metabolites of microbial activity, which caused the increase of free water relative content in fresh brown rice noodles (Yang et al, 2021; Zheng et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, microbial activity destroyed the gel structure of fresh brown rice noodles, and this might weaken the binding ability between water and macromolecules; thus, the strongly bound water was shifted into weakly bound water and free water. On the other hand, water was one of the metabolites of microbial activity, which caused the increase of free water relative content in fresh brown rice noodles (Yang et al, 2021; Zheng et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, A 22 showed an upward trend as storage time increased, which indicated that some bound water was progressively transformed into weakly bound water. Zheng et al 25 . reported that the proportion of weakly bound water and free water in fresh wheat noodles increased during storage at 25 °C.…”
Section: Resultsmentioning
confidence: 99%
“…A 22 showed an upward trend as storage time increased, which indicated that some bound water was progressively transformed into weakly bound water. Zheng et al 25 reported that the proportion of weakly bound water and free water in fresh wheat noodles increased during storage at 25 °C. Interestingly, the percentage of free water in KGM-supplemented noodles also exhibited a rising trend with the prolonging of storage duration.…”
Section: Wileyonlinelibrarycom/jsfamentioning
confidence: 99%
“…This phenomenon was very obvious in the control group, which may be caused by the increase of TPC that accelerated the deterioration of noodles. As the QBFN deteriorated, the bound capacity between water and noodle matrixes weakened, resulting in the decrease of strong bound water and weakly bound water (Zheng et al, 2019). For the MW + ε-PL + CP group, the increase of free water peak area A 23 was slighter than that control.…”
Section: Changes Of Moisture Content Aw and Water State In Qbfn During Storagementioning
confidence: 90%